Wittgenstein, Religion and Deep Epistemic Injustice - Robert Vinten (Religions)
In his article ‘Epistemic Injustice and Religion’, Ian James Kidd raises the possibility that some epistemic injustices might be deep. To spell out exactly what might be involved in deep epistemic injustices, especially those involving religious worldviews, an obvious place to look is Wittgenstein’s work on religion. Careful reflection on Wittgenstein’s remarks in the ‘Lectures on Religious Belief’ and his late work collected in On Certainty will have implications for how we are to understand the relationships between belief and evidence and for the ways in which we might enrich our hermeneutical sensitivities, and so Wittgenstein’s remarks are helpful for understanding epistemic injustices more generally. This paper will focus on epistemic injustices involving Islamophobia since Islamophobia has, so far, been given little attention in the literature on epistemic injustice.